DEVELOPMENT OF NATURAL TOURISM OBJECT IN KOMODO NATIONAL PARK, WEST MANGGARAI REGENCY, EAST NUSA TENGGARA PROVINCE - Azmi Rahman; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Development is a way carried out for the management of attractions in order to increase the attraction offered, in order to develop to increase the number of visits. The purpose of this research to find out what are the potential tourist attractions in the Komodo National Park and to find out how the development of natural tourism objects in Komodo National Park, West Manggarai Regency, East Nusa Tenggara Province. This research adopted a qualitative method with an observative approach, the subjects of this research were the Head of the National Park Management Section Resort, Staff of the National Park Management Section, Ranger, Tour Operators, Tour Guides and tourists visiting the Komodo National Park. Data collections were done by observation, interview and documentation. Data analysis was performed by data reduction, data presentation, and conclusion drawing. The results of research drawn from the development of nature tourism from the product sides are In Situ, Total Experiences, Perishable and Non Recoverable. From observations made by the author, it seems to have proceeded on its own because several factors that become innovations, but there are still some developments that haven’t been carried out as well as possible. As for some inhibiting factors in this research in the form of problems with control so that the difficult of spatial and bureaucratic arrangements hasn’t been arranged. For this reason, writing about development of natural attractions in the Komodo National Park is expected to be a reference for relevant National Park Management section. Keywords : development, natural attractions, in terms of products, national park